A Case Study of Combined Drainage Consolidation-Preloading Methods for a Highway Subgrade on Peat Soils. (1st December 2020) - Gui, Yue; Liu, Shengjun; Qin, Xiaqiang; Wang, Jianfei
Abstract : A highway project of up to 100 km/h is currently being constructed between Colombo and Katunayake International Airport across a Sri Lankan muskeg area. At this site, peat deposit was initially 0.8∼15.3 m thick and was underlain by sand, clay, or gneiss. The ground improvement methods adopted in the project were combined drainage consolidation-preloading methods, pipe pile foundation, and geogrids. This paper provides a detailed insight into the implementation of combined drainage consolidation-preloading methods used in the project, including sand pile, gravel pile, and plastic drainage plate as the prefabricated vertical drains. Periodical field-level observations were taken during the ten years, including the construction and postconstruction periods. The results show that peat soils' consolidation coefficient has been increased several times to tens of times due to ground improvement. After removing the temporary surcharge, the highway embankments did not heave and was followed by long-term settlements totaling 1.3∼7.4 cm over the following seven years of observations. Analysis of the settlement records shows that combined drainage consolidation-preloading methods have helped accelerate drainage consolidation and reduce postconstruction settlement.